Generation Z’s Attitudes and Expectations in the Workplace and Their Implications for Education Policy in Indonesia - Gustine, Gin Gin (Muslim Education Review, 2024)
Generation Z (Gen Z) refers to those who were born between mid-1990s and mid-2010s or currently between 12 and 27 years’ old as per 2024. In many parts of the world, the number of Gen Z employees is growing as this generation has just entered the workforce after finishing college. There has been much research on Gen Z in their work environment, however research on Gen Z and its implications related to educational policy is very limited. Understanding Gen Z’s attitudes and expectations in the workforce helps leaders, educators and other stakeholders to develop curriculum or business plans tailored to their needs and characteristics. This research aims to investigate Gen Z’s attitudes and expectations in the workplace. Data were collected from a survey involving 138 Gen Z who are ready to enter the workforce and in their final year of their study from Indonesia, Thailand and Afghanistan, which is followed up by a focus group discussion. Findings from this study indicate that Gen Z can be described as critical, open-minded and financially literate. Their expectations in their future employment include having ‘smart-office’ technology while at the same time they express an interest in Corporate Social Responsibility. It is expected that the findings will help educators to reconceptualize curriculum and identify strategies in assisting this generation to further develop their potential while maintaining a positive work ethic and realistic expectations in their workplaces.